2009
DOI: 10.1211/jpp/61.03.0005
|View full text |Cite
|
Sign up to set email alerts
|

Novel formulation of solid lipid microparticles of curcumin for anti-angiogenic and anti-inflammatory activity for optimization of therapy of inflammatory bowel disease

Abstract: The degree of colitis caused by administration of DSS was significantly attenuated by colonic delivery of SLMs of curcumin. Being a nontoxic natural dietary product, curcumin could be useful in the therapeutic strategy for inflammatory bowel disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
3
24
0
2
Order By: Relevance
“…Treated group with SLM curcumin showed a faster weight gain than the DSS control additionally it showed predominance of eosinophils in the chronic cell infiltrate. The above in vivo studies showed that degree of colitis caused by administration of DSS was significantly attenuated by colonic delivery of SLMs of curcumin 36 .…”
Section: Fig 2: Release Mechanism Of Microparticlesmentioning
confidence: 84%
“…Treated group with SLM curcumin showed a faster weight gain than the DSS control additionally it showed predominance of eosinophils in the chronic cell infiltrate. The above in vivo studies showed that degree of colitis caused by administration of DSS was significantly attenuated by colonic delivery of SLMs of curcumin 36 .…”
Section: Fig 2: Release Mechanism Of Microparticlesmentioning
confidence: 84%
“…Previously described formulations include microsponges [10], microspheres [11], solid lipid microparticles [12], cyclodextrin complexes [13] and curcumin-inclusion complex tablets with pH-and enzyme-sensitive polymer coating [14]. While Beloqui et al [7] formulated curcumin-NPs using conventional synthetic poly (lactide-co-glycolide) (PLGA) and polymethacrylate (Eudragit ® S100), Gugulothu et al.…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability and biocompatibility of curcuminoids could be significantly improved, if administered intrarectal [13,14]. Conventional suppositories are solids at room temperature and melt or soften at body temperature, due to the characteristics; patients feel discomfort, and prefer oral administration of drugs, rather than via suppositories [15][16][17].…”
Section: Introductionmentioning
confidence: 99%